Hemifacial Microsomia in a Cat. (18th July 2017) - Song, R. B.; Kent, M.; Glass, E. N.; Davis, G. J.; Castro, F. A.; de Lahunta, A.
Summary: A 7‐month‐old domestic medium hair cat presented with facial asymmetry affecting the bony and soft tissue structures of the right side of the head including the maxilla, nose, eye and pinna of the ear. Additionally, neurological dysfunction of the facial and vestibulocochlear nerves on the affected side was present. A congenital malformation affecting the first and second embryologic pharyngeal arches was suspected. This is the first case of hemifacial microsomia of likely congenital origin reported in a cat.